CORRELATION OF mRNA ALPHA RECEPTOR ESTROGEN (ER⍺) AND BETA RECEPTOR ESTROGEN (ERβ) EXPRESSION IN ADENOMYOSIS - Juliana Putri Ridwan Gani, Rezky; Abdullah, Nusratuddin; Bangsawan, Nurbani; Alfian Zainuddin, Andi; Moeljono, Eddy; Bahar, Irnawati; Fitria, Monika (International Journal of Psychosocial Rehabilitation, 2020)
Adenomyosis is a condition in which endometrial tissue in the myometrium is hypertrophy and reactive. Adenomyosis is one of the gynecological problems that has an impact on a woman’s social life because of very painful symptoms during menstruation and infertility. The exact pathogenesis of adenomyosis is still unclear. The estrogen is thought to be involved in adenomyosis. Estrogen works on two estrogen receptors, ER⍺ and ERβ. Estrogen receptors are thought to be an important step in the occurrence of adenomyosis. The exact mechanism regarding the role of ERα and Erβ is still being investigated. Research that analyzes the comparison of ERα and Erβ mRNA expression on the incidence of adenomyosis has never been done in Indonesia. This study aims to analyze the correlation of mRNA ERα and ERβ expression in adenomyosis. Research was done at an educational hospital in Makassar from January to August 2019. an observational study with a cross-sectional study approach, a sample of 15 people diagnosed with adenomyosis and 15 people diagnosed not with adenomyosis. Tissues were examined in the Pathology Anatomy Laboratory and Erα/Erβ mRNA expressions in the Molecular Biology and Immunology Laboratory using the real-time PCR method. The result of this study is that ERα and ERβ mRNA expression increased in the adenomyosis group compared to the non-adenomyosis group. Pearson correlation showing strong positive correlation between ERα mRNA and ERβ mRNA expression with p-value of